Women's right and the gender question:appraisal of the journey so far in the light of CEDAW and the WCW beijing paltform in action (2000)
This paper appraises the journey so far n the achievement of women's right in the light of two international instruments namely: 1. The UN convention on the elimination of all forms of discrimination against women, popularly called CEDAW and 2. the Beijing platform of action which emanates from the world conference on women(WCW). For the purpose of this paper, these two international instruments will be referred to as CEDAW and the WCW beijing platform of action or simply as the platform for action. CEDAW is an international human right document that establishes internationa standards of equality between women and men. The convention was adopted by the UN general assembly on 18th December,1979, and entered into force as binding treaty on 3rd September, 1981. CEDAW abhors anything that can bring about unequal treatment between men and women while they are carrying out thier livelihood, describing the contarary as discrimination against women. CEDAW seeks the elimination of discrimination against women under the law (de jure) and in practice (de Facto). The WCW beijing platform for action as as human instrument reaffirms that the: advancement of women and the achievement of equality are a mtter of human rights and condition for social justice. In paragraphs 1-6 of its mission statement in chapter 1, the platform emphasizes that women and men share common concerns that can only be addressed by working together and in partnership towards the common goal of gender equity throughout the world. But has Nigeria and indeed many other countries really worked assiduously towards the achievement of the goal of gender equality? This paper in answering this and posting that the answer is in the negative, appraised a variety of issues concerning women's right across the globe in the light of conformity or otherwise with the provisions of CEDAW and the Beijing platform for action.